Cultural Strategy and Identity Construction in Chinese Emerging Brands' Global Expansion: The Case of Pop Mart - Zhao,Hanbing (2025)
This thesis takes Pop Mart as a representative to study how emerging Chinese brands participate in the construction of global identity through visual and emotional narratives. Under the guidance of postcolonial theory, this study analyzes how Pop Mart strikes a balance between cultural expression and global appeal by designing hybrid characters that integrate East Asian aesthetics with global visual styles. Through qualitative analysis of brand visuals, digital platform content, and character narratives, this study demonstrates how key ips (intellectual property) - Molly, Skullpanda, Dimoo, and labubu - convey a mixture of emotional ambiguity and symbolism. The research results highlight how small brands from non-Western backgrounds can utilize visual culture and emotional design to gain wide popularity and cultural support from global audiences in the international market. Furthermore, the research contributes to the interdisciplinary discussion of global brands by demonstrating how visual and emotional strategies can serve as tools for soft power and symbolic negotiations.
Keywords: PopMart; Chinese Branding; Cultural Hybridity; Postcolonial Theory; Global Identity; Visual Analysis